RSM-based optimization study on polysaccharide production by wild-Serbian Ganoderma applanatum strain (BGS6Ap) in a batch fermentation / Joshini Pillai Balamurugan - Joshini Pillai , Balamurugan (2021)
A wild-serbian ganoderma applanatum strain bgs6ap (gasb) from mount kosmaj, serbia was successfully isolated and molecularly identified. molecularly, gasb generated 651 base pairs that were sequenced and found to be a different strain of g. applanatum strain atcc and ganoderma sp. strain gps 047 in the same clade using ncbi-blast. one factor at a time (ofaat) method was implemented for growth curve and morphological analysis to study the temperature effect of the mycelium growth. reflecting on to its natural cold habitat in eastern europe, gasb favoured the temperature of 25°c for biomass, exopolysaccharide (eps) and endopolysaccharide (ens) production followed by 20°c and 30°c. morphologically verified, large dense mycelia pellets exhibited high (biomass-ens) and hairy starburst pellets (eps). growth curve analysis using liquid fermentation was conducted and differentiated based on the pellet formation that contributed to biomass (5.04 g/l), ens (0.51 g/l), eps (1.46 g/l) at temperature of 25°c (biomass, ens) and 20°c (eps). in response surface methodology, the applied central composite design proved that the experimental results were found to be significant for biomass and ens production. the results gave the optimized biomass (17.51 g/l), eps (2.59 g/l) and ens (3.47 g/l) production at day 15 (10g /l of glucose), initial ph 6, 24°c and 153 rpm. extracted eps, ens and glucan sulphate (gs) gave a confirmation spectral linkage in ftir (between 2928 cm-1 and 889cm-1) and nmr (δ 4.30 and 5.20 ppm) as exo-β-d-glucan and endo-β-d-glucan when compared with β-d-glucan standard of laminarin. this blueprint could be employed to achieve high biomass, eps and ens when subjected to high scale bioreactor system for other temperate medicinal mushrooms.